Chair and sofa dimensions based on body measurements of selected Filipinos in Metro Manila (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2005)
In the absence of a Filipino standard chair and sofa dimensions, local furniture maker borrow Western standards which are incompatible with the Filipino's physique. This anthropometric study is a pioneering effort in the Philippines, focused on design of chairs and sofas. It aimed to derive seat dimensions based on an anthropometric survey of 200 sample adult individuals. Body segments were measured using anthropometers, steel tape and ruler, and a custom-designed portable measuring chair. Statistical analysis, ergonomic computations and graphic analysis were used to derive changes in the commonly used seat dimensions in furniture design. These are 1) wider seat width for chairs from 410 mm to 480 mm; 2) lower seat height of chairs from 430 mm to 370 mm and sofa from 380 mm to 350 mm.; 3) lower armrest height of 150 mm from prevalent of 210 mm; 4) seat depth of 370 mm from 400 mm for chairs and 390 mm from 520 mm for sofa. Dimensions for lumbar support was derived which is a 15 mm-thick protrusion with an arc measured from 115 mm up to a height of 300 mm from the seat. With these new set of dimensions, this study recommends the need to review dimensional and structural features of the locally-made chairs and sofas in order to design seats truly 'fit' for the Filipino user.